AB1358 Body image satisfaction in rheumatic patients: Preliminary data. (23rd January 2014) - Cunha-Miranda, L.; Cardoso, A.; Donica, O.; Fernandes, R.
Abstract : Background: Physical disabilities can cause disturbances in a patient's body image.Body dissatisfaction has severe impact on obesity related psychological distress and other mental health problems. The recommendation to achieve optimal weight and body fat tissue has been an essential principle in the non-pharmacologic treatment of most rheumatic diseases. Objectives: This study aim is to evaluate body perception on rheumatic patients and its relation to body composition, pain and quality of life. Methods: Demographic information was recorded, quality of life was assessed by the Short Form-12 Health Survey (SF-12) (physical component score - PCS and mental component score - MCS), the body image perception was assessed by an adapted body shape questionnaire (BSQ) with 13 figures, and two visual analogue scales (VAS, value increase with body surface area) for the current and ideal appearance. Body composition was determined by octapolar bioimpedance (Inbody720). Results: A total of 96 patients from a rheumatology inpatient clinic, 95% female, mean age 61.5±11.9 years [34-91], 30% with rheumatoid arthritis (RA), 22% with connective tissue disease (CTD), 14.6% with Spondylarthritis, 14.6% with osteoarthritis (OA), 13.5% with SMED and 5% other diseases. The majority was overweight (36.5% pre-obese, 35.4% obese), with mean BMI of 28.3±5.7, no significant differences between diseases. Body fat (BF) average of 38.3% was higher in RA patients (42.1% GC; p=0.018). The visceral fat (VF) was increased in 80% of patients, especially in RA (89.7%; p=0.039). The current body image (CI-BSQ) was 7±3 figures, with higher value in RA (7.3) and the ideal appearance (IdI-BSQ) was 4±2, with a higher value in the CTD (4.4). The mean current image VAS was 46.5±25.8 (higher score means larger body surface area), with higher value in the RA (EVA: 51); mean ideal VAS appearance of 18.6±15.1, was higher in Spondylarthritis (EVA: 21). Spondylarthritis (Δ3.43±3.1) and RA (Δ3.38±2.7) patients presented the highest body shape difference between current and ideal appearance, while current and ideal VAS's variation was higher in RA (Δ31.5), SMED (Δ29.5) and CTD (Δ27.3). BMI was associated with higher CI-BSQ (r =0, 770, p<0.0001), IdI-BSQ (r =0, 306, p=0.002) and current VAS appearance (r =0, 607, p<0.0001). The BF was related to the current body image from both scales (r>0, 455, p<0.0001). Individuals with increased VF reported higher figure number in current image (p<0.0001), and CI VAS (p=0.001). There were no significant correlations with the quality of life. Conclusions: The BSQ was correlated to the corresponding VAS (current and ideal), as well as body composition variables. We observed an increased prevalence of overweight and obesity (72%) and a significant excess of body fat (38%) and visceral fat (80%), especially in patients with RA. Body image dissatisfaction was higher in RA, even when no difference in BMI between the studied diseases. Patients with higher BMI, increased body fat and visceral fat generally reported greater dissatisfaction with body image. The larger body image gap to ideal appearance was observed in RA patients, showing the significant dissatisfaction with body image. Measuring body dissatisfaction might provide a good tool to identify high risk groups to develop optimal intervention programs, for which rheumatic patients would significantly benefit due to their physical impairments. Disclosure of Interest: None Declared